The bad, the ugly and the good: new challenges for CSR communication. (7th April 2015) - Elving, Wim J.L.; Golob, Ursa; Podnar, Klement; Ellerup - Nielsen, Anne; Thomson, Christa
Abstract : Purpose: – This editorial is an introduction to the special issue on CSR Communication attached to the second CSR Communication Conference held in Aarhus (Denmark) in September 2013. The purpose of this paper is to critically evaluate the role of CSR communication and the development of theory and practice of CSR Communication in recent years. Design/methodology/approach: – The editorial sets up a research agenda for the future, the premises outlined about the role of CSR communication being based on Habermas' (1984) idea of instrumental/strategic and communicative action. Findings: – The theoretically based research shows that there are different framings of CSR. In the first framing, the business discourse is trying to institutionalize CSR and sustainability by pursuing CSR purely as a business case. In the second framing, alternative CSR discourses are challenging the business discourse, communication being oriented towards shared understanding. Originality/value: – The above findings are original insofar as they have implications for CSR communication scholars and practitioners. It is, for example, important that they acknowledge that two kinds of framings exist, and that they are interdependent. Hence, they should not fall into the trap of a critical discourse of suspicion where CSR communication is constantly criticized as a tool to serve business interests. In the context of strategic and/or communicative action, CSR communication occurs in different forms and for different purposes – either as informative, persuasive, aspirational and participatory type of CSR communication.